The Ex-pats Go to War: Hemingway, Paris and the Recovery of American Identity - Alolaiwi, Hayder Naji Shanbooj (Al-Adab Journal, 2023)
The present research is devoted to the post-WWI social and cultural milieu that made possible the intellectual and artistic effervescence characterizing the literary production of the American ex-pat writers in Paris during the 1920s and 1930s. The research is structured in an Introduction, four chapters, and Conclusion. After a necessary general presentation, the researcher goes deeper into the analysis of the identity crisis experienced by several American writers in exile, whom Gertrude Stein, herself an ex-pat, called “the Lost Generation” – among them, Ernest Hemingway, F. Scott Fitzgerald, John Dos Passos, Sinclair Lewis, and Samuel Putnam. Starting from the assumption that by discovering Europe, the American writers discovered themselves, the researcher chose Hemingway to represent the post-WWI generation of American ex-pats and followed the writer’s search for identity, seen as a process of singularization based on recognizing that we share a common origin or circumstances with another person or community. Ample space is devoted to Hemingway’s novel The Sun Also Rises, where a feeling of uselessness and nonsense accompanies the characters. Having (re)discovered their identity in Paris, many returned to their native America, rediscovering her as more disappointing than expected.